Effect of sintering on hydroxyapatite/sodium alginate properties - Kanasan, Nanthini; Sharifah Adzila, Syed Abu Bakar; Mustaffa, Nor Azimah; Abdol Rahman, Mohd Nasrull; Hassan, Mohd Fahrul; Panerselvan, Gurubaran (UTHM Publisher, 2018)
In the present work, a precipitation method was used to prepare a nanocomposite powders consisting of hydroxyapatite and sodium alginate by varying the composition of sodium alginate. The characterization of powder are analyzed by using Field Emission Scanning Electron Microscopy (FESEM) and X-ray diffraction (XRD). FESEM is used to identify the morphology and agglomeration of sintered samples while, XRD analysis is used to identify the phase of samples with an increase in the composition of sodium alginate up to 10%. Green samples were prepared and sintered at temperature 1000˚C and 1100˚C and the sintered samples are studied based on their phase stability, density and Vickers hardness .The result indicates that there is no secondary phase change happen in this XRD result. The density of HA/SA are increasing relative to hardness for composition ratio 99.5/0.5%. The maximum density were attained by 99.5/0.5% (HA/SA) at 2.12g/cm3 and 2.16g/cm3 for 1000˚C and 1100˚C respectively while, the maximum hardness were also attained by 99.5/0.5% for temperature 1000°C and 1100°C at 0.53GPa and 0.62GPa respectively. FESEM images of pure hydroxyapatite are fully dispersed in sodium alginate and the particles size are in agglomerate conditions. The aims of this research is to identify the effect of sintering on physical and mechanical properties of HA/SA.